Recurrent adenoid cystic carcinoma of the vulva: A case report of salvage stereotactic ablative radiotherapy to the pudendal nerve - Hanya Irfan, MBBS, BSc; Yusuf Ben-Tarifite, BMBCh, BA; Rana Mahmood, MBBS (Radiology Case Reports)
Adenoid cystic carcinoma (ACC) is an indolent malignancy that frequently recurs and particularly involves surrounding nerves which complicates management. ACC is mostly reported in the head-and-neck, but can also arise in the pelvis where treatment strategies are less established due to its rarity. In this case report a 44-year-old patient with previously treated vulval ACC presented with an isolated recurrence along the dorsal branch of the pudendal nerve. The pudendal nerve was successfully treated with salvage stereotactic ablative radiotherapy (SABR), with no evidence of active disease at 1-year follow-up. There is a potential role for SABR as an effective treatment for recurrent ACC with perineural spread, particularly when surgical options are limited. This case highlights the necessity of individualized treatment planning in rare anatomical presentations of ACC, with consideration for balancing oncological control with aim to preserve function. This report contributes to the limited literature on vulvar ACC and supports the integration of adjuvant radiotherapy into the multidisciplinary management.